Empathy is associated with interpersonal emotion regulation goals in everyday life - Geiger, Eva J.; Prüßner, Luise; Barnow, Sven; Joormann, Jutta (Emotion, 2024)
Responding to the emotions of the people around us is a phenomenon traversing human lives; however, research has only recently started exploring the predictors of interpersonal emotion regulation (IER). In two ecological momentary assessment studies conducted in 2021 and 2022, we tested whether facets of empathy (i.e., mentalizing, experience sharing, empathic concern, and personal distress) are associated with other-focused IER goals and their attainment in everyday life (Ns = 125 and 204). Study 1 examined associations between mentalizing, experience sharing, and global hedonic and counter-hedonic IER goals (i.e., making others feel better or worse) in a relatively young and predominantly female student sample in Germany. Study 2 expanded these findings to empathic concern, personal distress, and specific types of hedonic and counter-hedonic IER goals (i.e., increasing, decreasing, and/or maintaining others’ positive and/or negative emotions) in a more diverse U.S. community sample. Participants primarily endorsed hedonic IER goals, which were associated with higher mentalizing and experience sharing in both studies and higher empathic concern and lower personal distress in Study 2. Counter-hedonic IER goals were positively associated with experience sharing and personal distress in Study 2. Conversely, empathic concern and mentalizing were negatively related to counter-hedonic IER goals. We also found differential associations for state and trait empathy with IER goals. All empathy facets except personal distress were positively associated with goal attainment in Study 2. These findings address a major gap in our knowledge about everyday IER and offer a novel perspective on empathy in social emotion regulation processes. (PsycInfo Database Record (c) 2023 APA, all rights reserved)